A CRITICAL DISCOURSE ANALYSIS AND ILLOCUTIONARY ACTS OF JOHN MAYâS SPEECH IN THE DUKE OF EDINBURGHâS CEREMONY AWARD - Prescilla, Yesvika Fibry; Amalia, Resti (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractThe aim of this article is to investigate John Mayâs speech in The Duke of Edinburghâs ceremony award in Indonesia. This study was designed based on descriptive qualitative research using critical discourse analysis approach, focusing on illocutionary acts under the speech acts theory. The video of speech was transcribed and analyzed to gain the deep insight of the speech. The result showed that speaker addressed not the audiences only but also all the people in the world. The purposes of John Mayâs speech are to congratulate the awardees in completing the program and then achieving the award, to encourage all the audiences, and to convince young people, especially the one who joined the award. The speakerâs feelings through the speech are happy, satisfied, excited, proud, and confident/sure. Those expressions show no hidden agenda. The types of illocutionary acts that the speaker used are representatives, directives, commisives, expressive, and declaratives. However, mostly he used expressive speech acts in his speech in order to encourage other people.Â Keywords: Speech, Critical Discourse Analysis, Illocutionary Acts, Speech Acts, Expressive